ANALISIS PERAMALAN PENJUALAN PRODUK KECAP PADA PERUSAHAAN KECAP MANALAGI DENPASAR BALI - Padma Yanti, Ni Putu Lisna; Tuningrat, I.A. Mahatma; Suryawan Wiranatha, A.A.P.Agung (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 4 No 1 (2016): Maret, 2016)
Forecasting is an important tool for the company to be more effective and efficient. The purposes of this study were to determine the best forecasting method to forecast sales of soy sauce products, and to forecast sales of soy sauce in the future by using the best forecasting method at the Manalagi Soy Sauce Company in Denpasar. The study used four methods of forecasting, namely moving average, exponential smoothing, linear trend, and non-linear trend. Error level from each method was calculated by of Mean Absolute Deviation (MAD), Mean Squared Error (MSE), and Mean Absolute Percentage Error (MAPE). Results of the study show that the best forecasting method to forecast the sales of soy sauce at Manalagi Soy Sauce Company in Denpasar is trend linier method. This method has the lowest error compare to the other forecasting method, in forecasting sales of soy sauce bottle size 625 ml obtained MAD value of 1.984,54, MSE of 8.850.382,64, and MAPE by 2%, while for forecasting sales of soy sauce refill size 625 ml obtained MAD value of 2440.27, MSE of 8972737.56 and MAPE by 4%. Keywords: sales forecasting, time series method, soy sauce.
Keywords: 90